Sinergi Dakwah dan Pemberdayaan Masyarakat melalui Desa Binaan - Trisnawati, Ira; Aminuddin; Aflaha, Ardhina Nur; Ayub; Kanande, La Ode Mansabdar (IAIN Kendari, 2025)
Community service activities are one form of implementation of the Tri Dharma of Higher Education. The Da'wah Management Study Program plays an active role in building communities through a systematic and measurable da'wah approach. Through the Assisted Village program, this activity aims to create synergy between strengthening religious capacity and mosque-based community empowerment. The service method used is Participatory Action Research (PAR), which involves actively involving the community in the process of problem identification, intervention implementation, and evaluation. Materials provided in this activity include Tahsinul Qira'ah Guidance which will be held on July 14, 2024, Da'i Management which will be held on August 2, 2024, and Mosque Financial Management which will be held on August 16, 2024. This activity is expected to improve the quality of community Qur'an reading, establish effective da'wah organizational management, and improve mosque financial governance in a transparent and professional manner. Keywords : Da'wah, Community Empowerment, Fostered Village